Considerations about of the medical specialized language: lexical-semantic - Yurima Hernández de la Rosa; Francisco Luis Moreno Martínez; Ana Vivian Fernández Peraza (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
The medical language specialized is one of the languages that bigger complexity presents at the present time, determinated mainly, for the scientific development and technician or the medicine. As systems inherent in the evolution of all scientific knowledge, the medical language did not escape the multiple influences that become very evident in the lexicon-semantic plane of the language. Some considerations on the linguistic phenomena that most evidenced in this plane, due in fact to the Anglo-Saxon influence in our language.